Ruminal fermentation of Nellore steers fed crude glycerine replacing starch vs. fibre-based energy ingredient in low or high concentrate diets - Lage, Josiane Fonseca; Vito, Elias San [UNESP]; Reis, Ricardo De Andrade [UNESP]; Delevatti, Lutti Maneck [UNESP]; Pierre, Norman Saint; Berchielli, Telma Teresinha [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2017)
Twelve ruminally cannulated steers (401.0 ± 41.5 kg) and 24 mo were used in a replicated arrangement truncated Latin Square with six animals in six treatments and four periods to evaluate the effect of crude glycerine (CG; 80.3% of glycerol) with starch or fiber-based energy ingredients in the concentrate on DMI, DM (DMD) and NDF digestibility (NDFD) and ruminal parameters. Experimental periods were 19 days (14 days for adaptation and 5 days to sampling). Diets were: CO - without CG and corn as ingredient of concentrate; CGC - inclusion of CG (10% of DM) with corn in the concentrate; and CGSH - inclusion of CG (10% of DM) with soybean hulls (SH) in the concentrate. All three diets were offered at low (LC) or high (HC) concentrate level, CL (40 or 60%). Animals fed LC or HC diets had similar DMI, DMD and NDFD. Animals fed diets with CG associated with corn or SH had higher propionate concentrations and lower A:P ratio. Diets with HC increase the propionate but do not affect the NDFD. CG (10% of DM) can be used to replace corn or SH in diets with 40 or 60% of concentrate, without affect NDFD.

Doze novilhos canulados no rúmen (401,0 ± 41,5 kg) e 24 meses de idade foram usados em delineamento de quadrado latino truncado replicado com seis animais, seis tratamentos e quatro períodos, para avaliar o efeito da glicerina bruta (GB; 80,3% de glicerol) com amido ou ingredientes energéticos a base de fibra no concentrado sobre o CMS, digestibilidade da MS (DMS) e FDN (DFDN) e parâmetros ruminais. O período experimental foi 19 dias (14 dias de adaptação e 5 dias de coleta). As dietas foram: CO - sem glicerina bruta e milho como ingrediente do concentrado; GBM - GB (10% da MS) com milho no concentrado; GBCS - GB (10% da MS) com casca de soja no concentrado. As três dietas foram ofertadas em baixo (BC) ou alto (AC) teor de concentrado (TC; 40 ou 60%). Animais alimentados com BC ou AC apresentaram similar CMS, DMS e DFDN. Animais alimentados com GB com milho ou CS apresentaram maior concentração de propionato e menor relação A:P. Dietas com AC aumentou a concentração de propionato mas não afetou a DFDN. GB (10% da MS) pode ser usada para substituir o milho ou CS em dietas com 40 ou 60% de concentrado, sem afetar a DFDN.
Fermentação ruminal de novilhos Nelore alimentados com glicerina bruta substituindo amido vs. ingrediente energético a base de fibra em dietas de baixo ou alto concentrado
Keywords: acetate; glycerol; propionate; pH; soybean hulls; acetato; glicerol; propionato; pH; casca de soja